2018
DOI: 10.1016/j.omtm.2018.06.002
|View full text |Cite
|
Sign up to set email alerts
|

An Isolated Limb Infusion Method Allows for Broad Distribution of rAAVrh74.MCK.GALGT2 to Leg Skeletal Muscles in the Rhesus Macaque

Abstract: Recombinant adeno-associated virus (rAAV)rh74.MCK.GALGT2 is a muscle-specific gene therapy that is being developed to treat forms of muscular dystrophy. Here we report on an isolated limb infusion technique in a non-human primate model, where hindlimb blood flow is transiently isolated using balloon catheters to concentrate vector in targeted leg muscles. A bilateral dose of 2.5 × 1013 vector genomes (vg)/kg/limb was sufficient to induce GALGT2-induced glycosylation in 10%–60% of skeletal myofibers in all leg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 55 publications
10
16
0
1
Order By: Relevance
“…49 Previous WFA and CT antibody-staining studies showed that both mouse (mdx and WT) and rhesus macaque (WT) cardiomyocytes have little, if any, endogenous expression of Galgt2-induced glycosylation and that the majority of such staining is confined to intercalated disks. 49,57 Delivering rAAVrh74.MCK.GALGT2 intravenously via the tail vein led to dose-dependent overexpression of the human GALGT2 transgene, with increased glycosylation evidenced by increased WFA staining ( Figures 1A-1C). WFA staining occurred along the entirety of the sarcolemmal membrane in mouse cardiomyocytes, which were marked by co-staining with an antibody to laminin a2 ( Figure 1B).…”
Section: Dose Study Of Raavrh74mckgalgt2-induced Cardiomyocyte Glycmentioning
confidence: 99%
“…49 Previous WFA and CT antibody-staining studies showed that both mouse (mdx and WT) and rhesus macaque (WT) cardiomyocytes have little, if any, endogenous expression of Galgt2-induced glycosylation and that the majority of such staining is confined to intercalated disks. 49,57 Delivering rAAVrh74.MCK.GALGT2 intravenously via the tail vein led to dose-dependent overexpression of the human GALGT2 transgene, with increased glycosylation evidenced by increased WFA staining ( Figures 1A-1C). WFA staining occurred along the entirety of the sarcolemmal membrane in mouse cardiomyocytes, which were marked by co-staining with an antibody to laminin a2 ( Figure 1B).…”
Section: Dose Study Of Raavrh74mckgalgt2-induced Cardiomyocyte Glycmentioning
confidence: 99%
“…rAAVrh74.MCK. GALGT2 is a muscle-specific gene therapy designed to overexpress the human GALGT2 transgene (also called B4GALNT2 ) in heart and skeletal muscle, where it acts as a β1,4 N-acetylgalactosaminyltransferase to glycosylate α dystroglycan 1, 2, 3, 4, 5, 6, 7, 8, 9. In adult skeletal muscle, expression of GALGT2 is confined to the neuromuscular and myotendinous junction, and its expression is also very low in the heart 10, 11, 12.…”
Section: Introductionmentioning
confidence: 99%
“…We chose to compare two intra-vascular delivery protocols that have been previously published as efficacious routes of AAV administration to large animal models (Table S1). The first method involves intra-arterial delivery with a double balloon catheter to the pelvic extremity, a method that has been successfully used in non-human primates 7 . Variations of the intra-arterial technique have also been successfully used for AAV delivery in both non-human primates and canine models (Table S1).…”
Section: Introductionmentioning
confidence: 99%